Advanced practice: a survey of current perspectives of Australian pharmacists. (June 2015) - Jackson, Shane; Martin, Grant; Bergin, Jennifer; Clark, Bronwyn; Halstead, Peter; Rowett, Debra; Stupans, Ieva; Galbraith, Kirstie; Yeates, Gilbert; Nissen, Lisa; Marty, Stephen; Gysslink, Paul; et al.
Abstract Background An Advanced Pharmacy Practice Framework for Australia (the 'APPF') was published in October 2012. Further to the release of the APPF, the Advanced Pharmacy Practice Framework Steering Committee planned to develop an advanced practice recognition model for Australian pharmacists. Aim To gauge the perspectives of the pharmacy profession relating to advanced practice, via an online survey, in order to inform the design of the model. Method A survey was developed and administered to Australian pharmacists through SurveyMonkey . The survey content was based on findings from a review of national and international initiatives for recognition of advanced practice in pharmacy and other health disciplines, including medicine and nursing. Results The results of the survey showed that a high proportion of respondents considered they were already working at, or working towards achieving, an advanced level of practice. The responses relating to the assessment methods showed a clear preference for 'submission of a professional portfolio'. A 'written examination' had a low level of support and in relation to an 'oral examination by a panel' there was a marked preference for a panel of multidisciplinary health professionals over a panel of pharmacists. Conclusion The survey outcomes will inform the development of an advanced pharmacy practice recognition model for Australian pharmacists, particularly in relation to the assessment methods. Survey outcomes also demonstrated that there is scope to further enhance the application of the APPF in the development and recognition of advanced practitioners, and to build greater awareness of the breadth of competencies encompassed by 'advanced practice'.